Discharge from triage: modelling the potential in different types of emergency department. Issue 2 (1st March 2003) - Cooke, M W; Arora, P; Mason, S
Abstract : Objective: To assess the potential for patients to be assessed and discharged directly from triage in an emergency department (ED). Methods: Modelling was undertaken by collection of retrospective electronic data from four different EDs. Serial removal of groups was undertaken using data from coding systems related to patients details of admission/treatment/investigations and procedure undertaken. The final group left were analysed for ambulance usage, prior primary care consultation, and age group. Results: 29.4% patients were discharged after clinical assessment but without any specific treatment or investigation. It was seen that of the patients who can be considered for discharge from triage, 15.5% were brought to the ED by ambulance, 3.5% were patients who had already consulted primary care, and 11% were children. Conclusions: This study suggests that a large percentage of patients seen in EDs may not require the extra facilities of that department. There is potential for a large number to be discharged within a few minutes of arrival if appropriate assessment skills are available at first contact. This may require more senior assessment than is currently used. This study has not assessed safety of such a system or the times of day when it is best deployed.